Diversidade genética em beldroegas Portulaca spp. - Souza, Jardel da Silva (2020)
The success of a breeding program relies on the genetic variability available. One way to access the variability present in a plant population is through its characterization. Portulaca umbraticola, a species widely used in urban ornamentation, lack studies on its ornamental and genetic potential. Knowing the genetic diversity of a species is very important for a breeding project that aims to provide material of quality for the ornamental plant market. This study aimed to evaluate the genetic diversity among twenty accessions of P. umbraticola and to confirm the taxonomic identification of these accessions by comparing them with P. oleracea, to indicate ideal accessions for programs of genetic improvement of the species. The twenty accesses were collected on public localities in the municipalities of Areia and Santa Rita, Paraíba. Plants were grown in 3L pots with a commercial substrate under a greenhouse environment in a completely randomized design. The experiment was carried out at the Laboratório de Citogenética Vegetal in the Centro de Ciências Agrárias of the Universidade Federal da Paraíba (CCA-UFPB). Twenty accesses were used. In the first chapter, 13 quantitative characters and 11 qualitative characters from the twenty accessions of P. umbraticula were used, data were submitted to the analysis of variance, mean test, multivariate analysis of variance, determined relative importance, analysis of canonical variables, and Scott test -Knott at 1% probability. All data were analyzed using the Genes program. In the second chapter, the twenty accessions of P. umbraticola and one access of P. oleracea were analyzed. A balanced diallel cross was also performed with 11 parentals without the reciprocal cross. In the first chapter the accessions 5, 6, 12, 13, 14, 18 and 19 are recommended. In the second chapter, it was found that all accession